Insights into the pathogenesis of gestational and hepatic diseases: the impact of ferroptosis - You, Yilan; Qian, Zhiwen; Jiang, Ying; Chen, Lingyan; Wu, Danping; Liu, Lu; Zhang, Feng; Ning, Xin; Zhang, Yan; Xiao, Jianping (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis, a distinct form of non-apoptotic cell death characterized by iron dependency and lipid peroxidation, is increasingly linked to various pathological conditions in pregnancy and liver diseases. It plays a critical role throughout pregnancy, influencing processes such as embryogenesis, implantation, and the maintenance of gestation. A growing body of evidence indicates that disruptions in these processes can precipitate pregnancy-related disorders, including pre-eclampsia (PE), gestational diabetes mellitus (GDM), and intrahepatic cholestasis of pregnancy (ICP). Notably, while ICP is primarily associated with elevated maternal serum bile acid levels, its precise etiology remains elusive. Oxidative stress induced by bile acid accumulation is believed to be a significant factor in ICP pathogenesis. Similarly, the liver’s susceptibility to oxidative damage underscores the importance of lipid metabolism dysregulation and impaired iron homeostasis in the progression of liver diseases such as alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), cholestatic liver injury, autoimmune hepatitis (AIH), acute liver injury, viral hepatitis, liver fibrosis, and hepatocellular carcinoma (HCC). This review discusses the shared signaling mechanisms of ferroptosis in gestational and hepatic diseases, and explores recent advances in understanding the mechanisms of ferroptosis and its potential role in the pathogenesis of gestational and hepatic disorders, with the aim of identifying viable therapeutic targets.